Take your pick! Examining decision-making behavior in athlete selection: a methodological description and pilot study - Johnston, K.; Baker, J. (Sport, Exercise, and Performance Psychology, 2025)
Traditional perspectives of human decision-making have illuminated the many "quirks" of the mind. While information regarding the number and scale of these phenomena is growing rapidly, there has been less discussion of why they may be there in the first place. A driving factor for this imbalance may be related to the methodological challenges that exist for rigorously and validly exploring these quirks in appropriate contexts. As such, the aims of this article were to (a) explore these methodological challenges, (b) develop an approach to evaluate athlete selectors` (coaches, scouts, administrators) decision-making behavior when assessing and selecting athletes, (c) pilot the approach to test selectors` decision-making in a mock selection environment, and (d) share the lessons learned from the pilot regarding the misuses, potential value, and opportunities for growth in this area. Our findings have implications theoretically and practically, as we illuminate the methodological concerns and challenges facing researchers in this area while presenting possible avenues forward.